2006
DOI: 10.1590/s0021-75572006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da função pulmonar em crianças e adolescentes no pré e pós-operatório de correção cirúrgica de valvulopatia reumática

Abstract: Objective: To assess pulmonary function in children and adolescents subjected to correction of rheumatic valve disease in order to quantify changes caused by factors inherent to surgery and rheumatic heart disease.Methods: This was a longitudinal and quantitative intervention study, undertaken at a children s hospital that is a center of excellence for the state of Pernambuco (Instituto Materno Infantil de Pernambuco), between December 2004 and May 2005. Eighteen children suffering from rheumatic fever and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…Th e drawing up and the selection of the envelopes were conducted by a person who was not involved in the recruitment and selection of patients in the study. Five repetitions of each techniques were performed and a Wright ® ventilometer (British Oxigen Company, London, England) was connected to the circuit of each equipment to measure the inspiratory capacity 20 . All the procedures were carried out under the guidance and supervision of the same physiotherapist, always in the morning, and the techniques were performed with the patient in the Fowler position of 45 degrees.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Th e drawing up and the selection of the envelopes were conducted by a person who was not involved in the recruitment and selection of patients in the study. Five repetitions of each techniques were performed and a Wright ® ventilometer (British Oxigen Company, London, England) was connected to the circuit of each equipment to measure the inspiratory capacity 20 . All the procedures were carried out under the guidance and supervision of the same physiotherapist, always in the morning, and the techniques were performed with the patient in the Fowler position of 45 degrees.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Indivíduos obesos, por exemplo, apresentam diminuição dos volumes pulmonares, bem como da complacência tóracopulmonar, pois a resistência imposta aos músculos inspiratórios aumenta a impedância do in luxo de ar para as vias aéreas. No presente estudo, as análises das variáveis antropométricas, como peso, altura e IMC, demonstraram a característica eutró ica dos indivíduos categorizados como saudáveis e hospitalizados (21,22).…”
Section: Resultsunclassified
“…There are few studies assessing the impairment of lung function after cardiac surgery in children. Caséca et al [32] showed that all pulmonary function parameters evaluated in the CCPO remained significantly deteriorated until five days after the intervention. Only minute ventilation (MV) returned to levels comparable to the preoperative from the 4th day of CCPO.…”
Section: Cardiac Surgery Postoperative (Ccpo)mentioning
confidence: 99%
“…The change of mechanical ventilation from the surgical incision, a situation found after sternotomy and the own anatomy and physiology resulting from the procedure, lead to decreased lung compliance in CCPO. In this situation, we recognize the importance of physiotherapy to restore function and prevent respiratory complications [32].…”
Section: Cardiac Surgery Postoperative (Ccpo)mentioning
confidence: 99%